2016
DOI: 10.1021/acs.iecr.5b03292
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Process Design for Oxidative Coupling of Methane (OCM): Comprehensive Reactor Engineering via Computational Fluid Dynamics (CFD) Analysis of OCM Packed-Bed Membrane Reactors

Abstract: The oxidative coupling of methane (OCM) reaction system was investigated in a packed-bed membrane reactor (PBMR) numerically via a comprehensive computational fluid dynamics (CFD) study. In this context, the complete set of momentum, mass, and energy balances were solved through finite-volume method in cylindrical coordinate system. The fractional-step method was utilized to decouple the reaction source terms from the convection-diffusion terms. The general observed trends for variation of the components’ conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…These measurements are consistent with other reported results [160][161][162] . However, the locally high temperatures apparently play no beneficial role on the process.…”
Section: Ocm Reactorssupporting
confidence: 94%
“…These measurements are consistent with other reported results [160][161][162] . However, the locally high temperatures apparently play no beneficial role on the process.…”
Section: Ocm Reactorssupporting
confidence: 94%
“… 1–5 Direct CH 4 conversion to ethylene (C 2 H 4 ) via oxidative coupling of methane (OCM) remains an active research frontier with ongoing studies in both catalysis science and reaction engineering. 6–9 Despite continued interest, the lack of the fundamental understanding of the structure–function relationships in the state-of-the-art OCM catalysts has prohibited industrial-scale application of OCM. 2,10,11 Recent work on selective OCM catalyst development chiefly focuses on the combinatorial screening of multicomponent mixed-phase catalyst systems as well as scrutinizing developed catalyst libraries using data science methods.…”
Section: Introductionmentioning
confidence: 99%
“…An older model study had previously shown that Na-coordinated WO 4 surface sites were more selective but slightly less active than Mncoordinated WO x and uncoordinated WO x sites during OCM in a series of model bi-metal oxide OCM catalysts 25. Lastly, via operando synchrotron μ-XRF/XRD/absorption-computed tomography, it was shown that crystalline manganese oxide phases including Mn 2 O 3 , Mn 7 SiO 12 and MnWO 4 are not required components to yield an active catalyst,6 while no conclusion could be reached regarding the dispersed phase Mn a O b surface sites that can be present on the SiO 2 30. The current study, utilizing in-situ spectroscopy, ab initio molecular dynamics, ab initio thermodynamics, and periodic-DFT modelling bridges the knowledge gap present in the literature and provides the following critical mechanistic insights, which suggest that Mn-promotion in fact is likely not essential for a yielding a selective-active OCM catalyst:1.…”
mentioning
confidence: 95%
“…This is expected to directly influence the C 2+ yield as the methane can be activated by the surface oxygen ionic species and the contribution of gas phase homogenous combustion reactions can be decreased. 16 Wang et al 17 studied the OCM reaction using a catalytic membrane reactor with a Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3Àd tubular membrane and a La-Sr/CaO catalyst packed-bed. Both, the packed-bed catalytic membrane reactor and the catalytic membrane reactor (i.e.…”
Section: Introductionmentioning
confidence: 99%